Rethinking the Bebras Challenge in Virtual Reality: Implementation and Usability Study of a Computational Thinking Game - Jelena Nakić; Ivana Rogulj; Lada Maleš (Multimodal Technologies and Interaction)
Virtual reality (VR) technology is becoming increasingly relevant as a modern educational tool. However, its application in teaching and learning computational thinking remains relatively underexplored. This paper presents the implementation of selected tasks from the international Bebras Challenge in a VR environment called ThinkLand. A comparative study was conducted to evaluate the usability of the developed game across two interface types: mobile devices and desktop computers. A total of 100 participants, including high school and university students, took part in the study. The overall usability rating was classified as “good”, suggesting that ThinkLand holds promise as a platform for supporting computational thinking education. To assess specific aspects of interface usability, a custom Virtual Environment Usability Questionnaire (VEUQ) was developed. Regression analysis was performed to examine the relationship between participants’ age, gender, and interface type with both learning performance and perceived usability, as measured by the VEUQ. The analysis revealed statistically significant differences in interaction patterns between device types, providing practical insights for improving interface design. Validated in this study, the VEUQ proved to be an effective instrument for informing interaction design and guiding the development of educational VR applications for both mobile and desktop platforms.